Should Replacement-Cost Changes Be Included in Income? - Samuelson, Richard A. (The Accounting Review, 1980)
Abstract ABSTRACT: In a replacement-cost accounting model, changes in the replacement-cost of assets held during a period are viewed by some as holding gains and losses which are includable in income for the period. The academic literature provides two alternative arguments in support of the holding gains treatment. One argument is that replacement-cost changes represent "cost savings"; the other argument is that replacement-cost changes may be used as "surrogates" for changes in net realizable value or discounted present value. The author of this paper examines the two arguments and concludes that neither is acceptable. He recommends that, if a replacement-cost model is used as a basis for financial reporting, replacement-cost changes be treated as direct adjustments to capital.